(untitled) (Research, Society and Development, 2022)
This research aims to analyze the challenges that arose through the implementation of the National Solid Waste Policy (PNRS) in light of the principle of sustainable development. In recent years, large impacts have arisen in Brazil as a result of the increased consumption of products generated by capitalism, and consequently the disposal of solid waste has aggravated environmental pollution, causing the government and society to worry about how to dispose of these waste. From this concern, Law 12,305/2010 was created, which gave rise to the PNRS where art. 6 of the aforementioned law provides for sustainable development as one of its guiding principles, which can be seen through several other standards, such as the management of the material cycle and the shared responsibility of polluters. The research was elaborated through the use of the deductive approach method, through bibliographic and documentary research. Through the results found, it was possible to verify that, although Law 12,305/2010 has been an important step in the search for solutions for the disposal of solid waste in recent decades, it is still not enough to solve the issue, considering that the municipalities they are not even putting into practice the determinations provided for in the aforementioned legal provision, and integrated action between the government, states and municipalities, as well as the contribution of private companies and the population in general, is essential.